The evolution of the concept of extraterritorial jurisdiction in international human rights based climate litigation (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Diagonal claims have become central in human rights based climate litigation before international courts and control bodies established by human rights treaties. Subjects located outside the country of origin of greenhouse gas emissions have attempted to assert the responsibility of such State for the violations of fundamental human rights. At the procedural level, this kind of disputes pose critical issues with regard to the assessment of jurisdiction and the extraterritorial application of human rights treaties. Both aspects will be analyzed in this article taking into account their evolution in climate change disputes.
Keywords: Human rights based climate litigation; diagonal claims; extraterritorial application of human rights treaties; extraterritorial jurisdiction